Porous composite sound absorbing material and its manufacturing method
The use of activated carbon cotton felt with adhered zeolite particles and rapid cooling technology in speakers enhances sound absorption and reduces costs, addressing limitations of conventional materials and improving low-frequency performance.
Patent Information
- Application Number
- JP2022578752
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2022-09-20
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2042-09-20
AI Technical Summary
Existing methods to enlarge the back chamber of speakers for improved low-frequency sound quality are limited by the use of materials with large pore diameters, high costs, and the inconvenience of using particulate materials like zeolite and activated carbon, which affect sound absorption performance and increase costs.
A porous composite sound absorbing material using activated carbon cotton felt with a large micropore structure and adhered zeolite particles, combined with rapid cooling and freeze-drying, to uniformly distribute zeolite particles and enhance sound absorption.
The material significantly improves low-frequency performance and stability of speakers by optimizing sound absorption, reducing costs, and ensuring uniform zeolite distribution, suitable for applications in consumer electronics.
Smart Images

Figure 0007617151000002 
Figure 0007617151000003 
Figure 0007617151000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of composite materials, and more particularly, the present invention relates to a porous composite sound absorbing material and a method for manufacturing the same. [Background technology]
[0002] With the rapid development of the consumer electronics industry and the dramatic improvement of people's living standards, consumers increasingly prefer smaller and flatter consumer electronic products. Meanwhile, people's requirements for sound are becoming higher and higher, and it is desirable to obtain better sound quality in an effective space. Therefore, the requirements for speakers are becoming more and more stringent.
[0003] Generally, the smaller the volume of the back chamber of a speaker, the worse the acoustic response in the low frequency range and the worse the acoustic expression such as sound quality. Therefore, it is necessary to devise a way to enlarge the back chamber of the speaker to further improve its low frequency range response.
[0004] In order to enlarge the back chamber of a loudspeaker, those skilled in the art provide various methods, such as the following methods: 1. Filling the back chamber with a gas with higher acoustic matching than air, such as carbon dioxide, etc. This method has the problem of poor long-term reliability due to the high difficulty in sealing the chamber. 2. Fill with sound-absorbing cotton, such as melamine foam, polyurethane foam, polyester sound-absorbing cotton, etc. However, the pore size of such materials is large, and the room for improving sound quality is limited. 3. Filling with porous materials such as activated carbon, zeolite, and silica to increase the volume of the virtual back chamber and improve the acoustic consistency of the gas in the back chamber. Such materials have a large amount of micro-pore structure, so the effect is significantly increased, but there are two problems. First, those with excellent sound absorption performance are often granular, which limits the use of speaker devices with complex back chambers. Second, the room for improvement by natural zeolite is limited, and secondary molding can significantly improve the effect, but the cost is high.
[0005] In response to the limitations of the above methods, those skilled in the art have made many attempts, for example, adding zeolite or activated carbon particles to sound-absorbing cotton or sound-absorbing fiber structure materials. This method not only improves performance, but also is easy to use because it is a block-shaped material. However, this method has obvious limitations. That is, the framework materials used are all general macro-pore structure materials, which have many functions such as dispersion, fixing, and support for sound-absorbing particles, but their contribution to the sound-absorbing performance of the porous composite sound-absorbing material is very limited, and in order to achieve good performance, it is necessary to always add a large amount of sound-absorbing particles such as zeolite or activated carbon particles, which not only significantly increases the cost, but also does not have a high upper limit on the sound-absorbing performance of the final material.
[0006] Therefore, there is a need in this field to provide a new method by which the back chamber of a speaker can be enlarged. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to improve the shortcomings of the prior art. Instead of using the traditional framework material, the present invention uses activated carbon cotton felt containing a large amount of micropore structure (framework material without a large amount of micropores includes sound-absorbing foam, sound-absorbing fiber, etc.), which can fix zeolite particles like ordinary framework material, has high dispersibility, and not only optimizes the sound-absorbing performance of zeolite particles, but also allows the large amount of micropore structure on the surface of activated carbon to work cooperatively with zeolite particles, so that the sound-absorbing performance of the final porous composite sound-absorbing material significantly surpasses both, and the cost is relatively low, with extremely high cost performance. [Means for solving the problem]
[0008] Specifically, the present invention provides a porous composite sound-absorbing material, which includes activated carbon cotton felt, zeolite particles and an adhesive; The activated carbon cotton felt is used as a skeleton material, and the zeolite particles are adhered to the fiber surface of the activated carbon cotton felt by an adhesive, so that the zeolite particles are uniformly dispersed and fixed. At the same time, a large number of micro-pore structures exist on the fiber surface of the activated carbon cotton felt, which can exert a synergistic effect with the zeolite particles, so that the sound absorption performance of the porous composite sound-absorbing material is significantly superior to that of both of them.
[0009] The activated carbon cotton felt used in the present invention is porous and has a specific surface area of generally 100 to 1800 m. 2 / g. The activated carbon fibers applicable to the activated carbon cotton felt of the present invention not only have abundant macropore structure, but also have a large number of micropores on the surface of the activated carbon fibers of the activated carbon cotton felt, the pore size of the macropores is generally 1 μm-1000 μm, preferably 100 μm-500 μm, the pore size of the micropores is less than 2 nm, and the micropore ratio is 5%-95%.
[0010] The particle size of the zeolite particles that can be used in the present invention is generally 50 nm to 1 mm, preferably 50 nm to 500 μm, and more preferably 100 nm to 100 μm. The zeolite particles may be fine powder, particles, or secondary molded zeolite particles.
[0011] In a preferred embodiment, the activated carbon cotton felt accounts for 5% by mass to 90% by mass, preferably 10% by mass to 50% by mass, the zeolite particles account for 1% by mass to 85% by mass, preferably 20% by mass to 60% by mass, and the adhesive accounts for 1% by mass to 30% by mass, preferably 5% by mass to 20% by mass, of the porous composite sound-absorbing material.
[0012] The adhesive used in the present invention may be one or more of an acrylic ester adhesive, a styrene butadiene adhesive, a polyurethane adhesive, an epoxy adhesive, and a silicone adhesive. The acrylic ester adhesive may be selected from a methyl acrylate adhesive, an ethyl acrylate adhesive, a butyl acrylate adhesive, an isooctyl acrylate adhesive, a methyl methacrylate adhesive, an ethyl methacrylate adhesive, and a combination thereof. The styrene butadiene adhesive may be selected from a high-temperature emulsion polymerization styrene butadiene rubber and a low-temperature emulsion polymerization styrene butadiene rubber, and a combination thereof. The polyurethane adhesive may be selected from a polyisocyanate adhesive, an isocyanate group-containing polyurethane adhesive, a hydroxyl group-containing polyurethane adhesive, a polyurethane resin adhesive, and a combination thereof. The epoxy adhesive may be a cold-curing adhesive, a heat-curing adhesive, or a light-curing adhesive. The silicone adhesive is a silicone resin-based adhesive or a silicone rubber-based adhesive.
[0013] The dispersion aid used in the present invention may be one or more of cationic surfactants, anionic surfactants, zwitterionic surfactants, and nonionic surfactants. Preferably, the cationic surfactant is a quaternary ammonium salt type surfactant, such as octadecyltrimethylammonium chloride, cetyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, etc., and preferably, the anionic surfactant is a sulfonate type surfactant or a sulfate ester salt type surfactant, and the sulfonate type surfactant is, for example, sodium dodecylbenzenesulfonate, etc. Examples of the sulfate ester salt type surfactant include, but are not limited to, sodium lauryl sulfate, etc.; examples of the zwitterionic surfactant include, but are not limited to, dodecylaminopropionic acid, hexadecyldimethylbetaine, octadecyldicarboxybetaine, octadecylhydroxypropylsulfobetaine, dodecylsulfobetaine, etc.; and examples of the nonionic surfactant include, but are not limited to, glyceryl monostearate, sorbitan laurate, sorbitan palmitate, sorbitan stearate, sorbitan tristearate, sorbitan oleate, sorbitan trioleate, etc.
[0014] The present invention further provides a method for producing the porous composite sound-absorbing material of the present invention, the method comprising the following steps S1 to S8: S1: Activated carbon cotton felt surface treatment By performing surface treatment on activated carbon cotton felt, the sound absorbing performance is improved and the wettability with the sound absorbing solution is increased. S2: Manufacturing of sound-absorbing solution Zeolite particles, adhesive, dispersing agent, foaming agent and dispersing agent are mixed to obtain a sound-absorbing raw solution. S3: Soaking The sound-absorbing raw solution obtained in step S2 is used to soak the activated carbon cotton felt treated in step S1 to obtain a zeolite-activated carbon cotton felt composite material; S4: Fixed form The zeolite-activated carbon cotton felt composite material obtained in the immersion step S3 is quenched to shape the zeolite-activated carbon cotton felt composite material; S5: Dispersant removal The dispersant contained in the zeolite-activated carbon cotton felt composite material shaped in step S4 is removed by freeze-drying; S6: hardened The zeolite-activated carbon cotton felt composite material from which the dispersant has been removed in step S5 is fired under conditions that allow the adhesive to be hardened, thereby hardening the adhesive contained in the zeolite-activated carbon cotton felt composite material; S7: Cleaning The mixture was ultrasonically washed several times with water to remove residual dispersing agent, foaming agent and loosely adhered zeolite particles. S8: Dry After drying the water, the porous composite sound absorbing material is obtained.
[0015] When the porous composite sound-absorbing material according to the present invention is applied to a speaker, it is preferable to first cut the activated carbon cotton felt according to the shape of the back chamber of the speaker before carrying out the surface treatment step S1.
[0016] According to the method of the present invention, in the surface treatment step S1, the activated carbon cotton felt can be surface-treated by one or more methods selected from plasma treatment, corona treatment, oxidation treatment, reduction treatment, acid treatment, alkali treatment, surfactant solution immersion, and solvent immersion.
[0017] Preferably, the activated carbon cotton felt is surface-treated by an oxidation treatment method. Preferably, the oxidation treatment is performed by a baking method, for example, baking can be performed using a fan oven, the baking temperature is generally 100 to 300°C, and the baking time is generally 0.5 to 5 hours.
[0018] Before the surface treatment, the activated carbon cotton felt can be first thoroughly washed with a solvent, for example, by immersing the activated carbon cotton felt in a solvent, the immersion time is generally 1 to 24 hours, and the solvent is preferably a low-boiling organic solvent compatible with water, which may be one or more of methanol, ethanol, acetone, tetrahydrofuran, etc. After the activated carbon cotton felt is completely immersed in the solvent, the solvent can be removed by a drying method to obtain a dried activated carbon cotton felt.
[0019] According to the method of the present invention, the definitions of the zeolite particles, adhesive and dispersing aid used in step S2 of preparing the sound-absorbing raw solution are the same as those in the porous composite sound-absorbing material of the present invention, the foaming agent used in step S2 may be one or more of a physical volatilization type foaming agent, a thermal decomposition type foaming agent, an azo compound type foaming agent, a bicarbonate type foaming agent and a two-component reaction type foaming agent, and the dispersing agent used in step S2 is preferably water.
[0020] The physically volatile blowing agent applicable to the present invention is, for example, a low-boiling organic solvent that is compatible with water, but is not limited thereto. Such an organic solvent may be one or more of ethanol, acetone, methanol, isopropanol, tetrahydrofuran, etc.
[0021] Examples of the thermal decomposition type blowing agent applicable to the present invention include, but are not limited to, persulfide blowing agents, azo compound blowing agents, and bicarbonate blowing agents.
[0022] Such persulfides herein may be one or more of potassium persulfate, ammonium persulfate, etc., such azo compounds herein may be one or more of azodicarbonamide, azobisisobutyronitrile, etc., and such bicarbonates herein may be one or more of sodium bicarbonate, potassium bicarbonate, etc.
[0023] The two-component reactive foaming agent applicable to the present invention is not limited to one or more of, for example, carbonate+hydrochloric acid, bicarbonate+hydrochloric acid, and the like.
[0024] The carbonate salt may be one or more of sodium carbonate, potassium carbonate, calcium carbonate, barium carbonate, etc., but is not limited thereto, and the bicarbonate salt may be one or more of sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, barium bicarbonate, etc., but is not limited thereto.
[0025] In the step S2 of preparing the sound-absorbing stock solution, generally, 100 parts of zeolite particles, 1 to 200 parts of adhesive, 1 to 50 parts of dispersion aid, 1 to 50 parts of foaming agent, and 50 to 9900 parts of dispersant are mixed to obtain the sound-absorbing stock solution. In a preferred embodiment, in the step S2, 100 parts of zeolite particles, 5 to 20 parts of adhesive, 3 to 40 parts of dispersion aid, 7 to 40 parts of foaming agent, and 135 to 1800 parts of dispersant are mixed to obtain the sound-absorbing stock solution.
[0026] According to the method of the present invention, in the immersion step S3, any method in the present field can be adopted to achieve immersion, as long as the activated carbon cotton felt can be completely immersed in the sound-absorbing raw liquid. For example, the surface-treated activated carbon cotton felt can be immersed in the sound-absorbing raw liquid for 1 to 24 hours. When using means such as ultrasound or vacuum evacuation, the immersion can be accelerated and the immersion time can be shortened to 1 to 60 minutes.
[0027] Preferably, before molding, first remove excess sound-absorbing raw liquid on the surface of the zeolite-activated carbon cotton felt obtained in step S3, for example, by lightly wiping the surface to quickly remove excess sound-absorbing raw liquid.
[0028] According to the method of the present invention, in the molding step S4, any common quenching technique in the art can be adopted to quench the zeolite-activated carbon cotton felt composite material obtained in step S3 in a low-temperature environment and mold it. The quenching means can be a cooling device or a refrigerant.
[0029] According to the method of the present invention, in step S5 of removing the dispersant, freeze-drying can be performed using a freeze-dryer, and the freezing temperature and time are not particularly limited as long as the dispersant, such as water, in the zeolite-activated carbon cotton felt composite material can be completely removed.
[0030] According to the method of the present invention, the curing conditions adopted in the curing step S6, i.e., the baking time and temperature, are determined according to the specific adhesive adopted, and are generally not particularly limited, as long as the adhesive can be completely cured and the zeolite particles can be firmly attached to the fiber surface of the activated carbon cotton felt.
[0031] According to the method of the present invention, in the washing step S7, washing can be performed by any method known in the art, and preferably, washing can be performed by an ultrasonic cleaner, and the number and time of washing are not limited, as long as the residual dispersion aid, foaming agent, and zeolite particles that are not firmly attached can be removed. Preferably, the water used for washing is deionized water.
[0032] According to the method of the present invention, in the drying step S8, any method known in the art can be used to dry off the moisture, for example, drying in an oven, the drying temperature is generally 80-150°C, and the drying time is generally 0.5-2 hours.
[0033] Furthermore, the present invention further provides a loudspeaker, the back chamber of the loudspeaker comprising the porous composite sound-absorbing material according to the present invention.
[0034] The present invention adopts activated carbon cotton felt as a skeleton material, and compared with conventional materials such as sound-absorbing cotton and sound-absorbing fibers, the activated carbon cotton felt has a superior sound-absorbing performance due to the presence of a large number of micropore structures, and even if a small amount of zeolite material is used, the sound-absorbing performance is very excellent, so that the cost performance is higher.
[0035] In addition, in the manufacturing process of the porous composite sound-absorbing material of the present invention, by adopting rapid cooling molding and freeze-drying technology, the zeolite particles can be uniformly distributed in the activated carbon cotton felt, solving the problem that the distribution of zeolite is uneven and the loading depth is limited in the conventional process due to gravity or the viscosity of the sound-absorbing raw solution, etc., so that the sound-absorbing performance of the composite material is greatly improved and the problem that particulate materials such as zeolite and activated carbon cannot be applied to complex speaker chambers is solved. Effect of the Invention
[0036] After the back chamber of the speaker is filled with the porous composite sound-absorbing material of the present invention, the low frequency performance of the speaker can be greatly improved and its performance can be more stable. Since the acoustic speaker is applied in the fields of mobile phones, earphones, computers, automobiles, televisions, audio equipment and the like, the present invention can be applied in a wide range of fields.
[0037] These and other objects, aspects and advantages of the present disclosure will become apparent based on the following description and drawings of the present disclosure. [Brief description of the drawings]
[0038] [Figure 1] 1 is a schematic diagram of the structure of the porous composite sound-absorbing material of the present invention; [Diagram 2] SEM photographs of oxidized activated carbon cotton felt, in which the small image on the left shows the front view and the small image on the right shows the side view. [Diagram 3] 1 is a SEM photograph of the porous composite sound-absorbing material prepared in Example 1 of the present invention, in which the small image on the left shows the front and the small image on the right shows the side. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] The present invention uses activated carbon cotton felt as a framework material, and adheres zeolite particles to the fiber surface of the activated carbon cotton felt with an adhesive. Through quenching molding, freeze-drying and high-temperature treatment, a new porous composite sound-absorbing material is prepared, the structure of which is shown in FIG. 1.
[0040] The activated carbon cotton felt adopted by the present invention has a large number of micropores, and its sound absorption performance is obviously superior to that of sound-absorbing cotton and sound-absorbing fibers that only have a macroporous structure. After undergoing zeolite modification with better sound absorption performance, and combined with quenching molding technology to significantly improve the distribution uniformity of zeolite, the present invention greatly reduces the cost and solves the technical problem of the inconvenience of using particulate materials such as zeolite. The porous composite sound-absorbing material of the present invention further improves the sound absorption performance of the activated carbon cotton felt, so that after the porous composite sound-absorbing material of the present invention is filled into the back chamber of a speaker, its low-frequency performance can be significantly improved.
[0041] The present invention will be further explained by the following examples. It should be understood that the specific examples described herein are merely used to explain the present invention, and are not intended to limit the present invention.
[0042] Preparation Examples Example 1: The activated carbon cotton felt has a macropore diameter of 1 μm to 1000 μm and a micropore diameter of less than 2 nm, and the specific surface area of the activated carbon cotton felt is 1300 m 2 / g and the micropore ratio is 80%. The activated carbon cotton felt is cut according to the shape of the speaker back chamber, and the mass of the cut activated carbon cotton felt is 30 parts, which is immersed in ethanol for 12 hours, and then baked at 110°C for 2 hours in a blower oven to remove the ethanol. The activated carbon cotton felt is baked at 200°C for 2h in a blower oven and then oxidized. The front and side of the activated carbon cotton felt are scanned with a scanning electron microscope (SEM), and the SEM photographs obtained are shown in Figure 2, where the small image on the left shows the front and the small image on the right shows the side. The acoustic performance data is shown in Table 1. Using a magnetic stirrer, uniformly mix 100 parts of zeolite particles with a particle size of 0.2 to 20 μm, 20 parts of styrene butadiene adhesive, 10 parts of sodium lauryl sulfate, 40 parts of potassium persulfate, and 1,800 parts of water, calculated by mass, to produce a sound-absorbing concentrate for use. The above-mentioned oxidation-treated activated carbon cotton felt is put into the sound-absorbing solution and subjected to ultrasonic treatment for 1 hour. Next, the activated carbon cotton felt that has been completely infiltrated is taken out, the excess sound-absorbing solution on the surface is lightly wiped off with filter paper, and then it is rapidly cooled in a low-temperature environment (a cooling device or a refrigerant can be used) to be shaped. After the rapid cooling process is completed, the material is freeze-dried using a freeze dryer to completely remove the moisture in the material. After freeze-drying is complete, the styrene-butadiene adhesive is completely cured by baking in an oven at 110° C. for 2 hours. Using an ultrasonic cleaner, wash with deionized water five times, each time for 10 minutes, to remove residual foaming agent, surfactant, and zeolite particles that are not firmly attached. Then, bake in an oven at 110°C for 1 hour to obtain a block-shaped porous composite sound-absorbing material. The front and side of the obtained porous composite sound-absorbing material were scanned by a scanning electron microscope, and the SEM photographs obtained are shown in Figure 3. As can be clearly seen from the figure, the zeolite particles have already been firmly bonded to the fiber surface of the activated carbon cotton felt. The acoustic performance data is shown in Table 1.
[0043] Example 2 The activated carbon cotton felt used in this embodiment is exactly the same as that in the first embodiment. The activated carbon cotton felt is cut according to the shape of the speaker back chamber, and the mass of the cut activated carbon cotton felt is 30 parts, which is immersed in ethanol for 12 hours, and then baked at 110°C for 2 hours in an oven to remove the ethanol. The piece is baked at 200℃ for 2 hours in a fan oven for oxidation treatment. Using a magnetic stirrer, uniformly mix 100 parts of zeolite particles with a particle size of 0.2 to 20 μm, 10 parts of organic silica gel adhesive, 15 parts of sodium dodecylbenzenesulfonate, 20 parts of ammonium persulfate, and 550 parts of water, calculated by mass, to produce a sound-absorbing concentrate for use. The above-mentioned oxidation-treated activated carbon cotton felt is put into the sound-absorbing raw liquid and subjected to ultrasonic treatment for 1 hour. Next, the activated carbon cotton felt that has been completely infiltrated is taken out, the excess sound-absorbing raw liquid on the surface is lightly wiped off with filter paper, and then it is rapidly cooled in a low-temperature environment (a cooling device or a refrigerant can be used) to be shaped. After the rapid cooling process is completed, the material is freeze-dried using a freeze dryer to completely remove the moisture in the material. After freeze-drying is completed, the organic silica gel adhesive is completely hardened by baking in an oven at 110° C. for 2 hours. The mixture is washed five times with deionized water using an ultrasonic cleaner, with each washing time being 10 minutes, to remove residual foaming agent, surfactant, and zeolite particles that are not firmly attached. The mixture is then baked in an oven at 110°C for 1 hour to obtain a block-shaped porous composite sound-absorbing material. The front and side of the obtained porous composite sound-absorbing material are scanned by a scanning electron microscope, and the obtained SEM photograph (not shown) is basically the same as the SEM photograph of the porous composite sound-absorbing material of Example 1. It can be seen clearly from the figure that the zeolite particles are firmly attached to the fiber surface of the activated carbon cotton felt. The detailed data of its acoustic performance are shown in Table 1.
[0044] Example 3 The activated carbon cotton felt used in this embodiment is exactly the same as that in the first embodiment. The activated carbon cotton felt is cut according to the shape of the speaker back chamber, and the mass of the cut activated carbon cotton felt is 30 parts, which is immersed in ethanol for 12 hours, and then baked at 110°C for 2 hours in a blower oven to remove the ethanol. The piece is baked at 200°C for 2 hours in a fan oven and then oxidized. Using a magnetic stirrer, 100 parts of zeolite particles with a particle size of 0.2 to 20 μm, 15 parts of acrylic ester adhesive, 3 parts of sodium dodecylbenzenesulfonate, 7 parts of sodium hydrogen carbonate, and 135 parts of water are mixed uniformly by mass to produce a sound-absorbing concentrate for use. The above-mentioned oxidation-treated activated carbon cotton felt is put into the sound-absorbing liquid and subjected to ultrasonic treatment for 1 hour. Next, the activated carbon cotton felt that has been completely infiltrated is taken out, the excess sound-absorbing liquid on the surface is lightly wiped off with filter paper, and then it is rapidly cooled in a low-temperature environment (a cooling device or a refrigerant can be used) to set it into a shape. After the rapid cooling process is completed, the material is freeze-dried using a freeze dryer to completely remove the moisture in the material. After freeze-drying is complete, the styrene-butadiene adhesive is completely cured by baking in an oven at 110° C. for 2 hours. The mixture is washed five times with deionized water using an ultrasonic cleaner, with each washing time being 10 minutes, to remove residual foaming agent, surfactant, and zeolite particles that are not firmly attached. The mixture is then baked in an oven at 110°C for 1 hour to obtain a block-shaped porous composite sound-absorbing material. The front and side of the obtained porous composite sound-absorbing material are scanned by a scanning electron microscope, and the obtained SEM photograph (not shown) is basically the same as the SEM photograph of the porous composite sound-absorbing material of Example 1. It can be seen clearly from the figure that the zeolite particles are firmly attached to the fiber surface of the activated carbon cotton felt. The detailed data of its acoustic performance are shown in Table 1.
[0045] <Acoustic performance measurement> According to the method of measuring the resonant frequency of the speaker, the porous composite sound-absorbing materials manufactured in Examples 1, 2 and 3 are respectively put into the application tool, and the reduction value of the resonant frequency (F0) is measured by an impedance analyzer, and the drop damage status of the porous composite sound-absorbing materials is tested by a drop test. Here, the F0 reduction value represents the degree to which the resonant frequency moves to low frequency. Generally, the larger the F0 reduction value, the better the low frequency performance of the speaker. The volume of the touring back chamber of the speaker used in the acoustic performance measurement is 0.4 cubic centimeters (abbreviated as 0.4cc), and the specific test results are shown in Table 1.
[0046] [Table 1]
[0047] According to the results of Table 1, the activated carbon cotton felt (skeleton material) of the present invention has a micro-pore structure, and its sound absorbing performance is much better than that of conventional skeleton materials (sound absorbing foam, sound absorbing fiber). After filling the tooling back chamber with the porous composite sound absorbing material of the present invention, the speaker F0 is reduced by 160Hz or more. After filling the back chamber with the porous composite sound absorbing material of Example 3, the speaker F0 is reduced by 271Hz, which is significantly better than the activated carbon cotton felt and Bass particles (the sound absorbing material with the best commercial use effect for speakers at present), and its low frequency performance is significantly improved. At the same time, the material price of the present invention is significantly lower than that of Bass, and the cost performance is extremely high. In addition, the speaker using the porous composite sound absorbing material of Example 1 has a slight powder fall, while the speakers using the porous composite sound absorbing material of Example 2 and the porous composite sound absorbing material of Example 3 have no powder fall.
[0048] The above content has described in detail the objectives, technical solutions and beneficial effects of the present invention, and it should be understood that the above description is only the embodiments and specific examples of the present invention, and does not limit the protection scope of the present invention, and any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention. [Explanation of symbols]
[0049] 1. Activated carbon fibers in activated carbon cotton felt in porous composite sound absorbing materials 2 Zeolite particles
Claims
1. A porous composite sound absorbing material comprising: The porous composite sound-absorbing material includes activated carbon cotton felt, zeolite particles and an adhesive; The activated carbon cotton felt is used as a skeleton material, and the zeolite particles are bonded to the fiber surface of the activated carbon cotton felt by the adhesive; The porous composite sound-absorbing material is characterized in that there are macropores with a pore size of 1 μm to 1000 μm between the activated carbon fibers of the activated carbon cotton felt, and there are a large number of micropores with a pore size of less than 2 nm on the surface of the activated carbon fibers of the activated carbon cotton felt, and the micropore ratio, which is the ratio of the specific surface area of the micropores to the specific surface area of the activated carbon cotton felt, is 5% to 95%.
2. 2. The porous composite sound-absorbing material according to claim 1, wherein the zeolite particles have a particle size of 50 nm to 1 mm.
3. The porous composite sound-absorbing material according to claim 1, characterized in that the activated carbon cotton felt accounts for 5% by weight to 90% by weight of the porous composite sound-absorbing material, the zeolite particles account for 1% by weight to 85% by weight of the porous composite sound-absorbing material, and the adhesive accounts for 1% by weight to 30% by weight of the porous composite sound-absorbing material.
4. The porous composite sound-absorbing material according to any one of claims 1 to 3, characterized in that the adhesive is one or more of an acrylic ester adhesive, a styrene butadiene adhesive, a polyurethane adhesive, an epoxy adhesive, and a silicone adhesive.
5. 2. A method for producing the porous composite sound absorbing material of claim 1, comprising the steps of: The method includes a step S1 of performing a surface treatment on the activated carbon cotton felt, a step S2 of producing a sound-absorbing raw solution, a step S3 of soaking, a step S4 of shaping, a step S5 of removing the dispersant, a step S6 of hardening, a step S7 of cleaning, and a step S8 of drying. In step S1, the surface of the activated carbon cotton felt is treated by one or more methods selected from plasma treatment, corona treatment, oxidation treatment, reduction treatment, acid treatment, alkali treatment, immersion in a surfactant solution, and immersion in a solvent, thereby increasing the wettability with the sound-absorbing raw solution; In step S2, the zeolite particles, the adhesive, the dispersing agent, the foaming agent and the dispersing agent are mixed to obtain a sound-absorbing raw solution; In step S3, the sound-absorbing raw solution obtained in step S2 is used to soak the activated carbon cotton felt treated in step S1 to obtain a zeolite-activated carbon cotton felt composite material; In the step S4, the zeolite-activated carbon cotton felt composite material obtained in the immersion step S3 is quenched to shape the zeolite-activated carbon cotton felt composite material; In step S5, the dispersant contained in the zeolite-activated carbon cotton felt composite material shaped in step S4 is removed by freeze-drying; In step S6, the zeolite-activated carbon cotton felt composite material from which the dispersant has been removed in step S5 is fired under conditions that allow the adhesive to be hardened, thereby hardening the adhesive contained in the zeolite-activated carbon cotton felt composite material; In step S7, the mixture is ultrasonically washed several times with water to remove residual dispersion aid, foaming agent and zeolite particles that are not firmly attached; In step S8, the porous composite sound-absorbing material is obtained by drying the moisture.
6. The method according to claim 5, characterized in that in step S2, 100 parts of zeolite particles, 1 to 200 parts of adhesive, 1 to 50 parts of dispersion aid, 1 to 50 parts of foaming agent, and 50 to 9900 parts of dispersant are mixed to obtain a sound-absorbing raw solution.
7. 6. The method according to claim 5, wherein the blowing agent is one or more of a physical volatilization type blowing agent, a thermal decomposition type blowing agent, and a two-component reaction type blowing agent.
8. 6. The method according to claim 5, wherein the dispersing aid is one or more of a cationic surfactant, an anionic surfactant, a zwitterionic surfactant, and a nonionic surfactant.
9. A speaker, A speaker, wherein a back chamber of the speaker comprises the porous composite sound-absorbing material according to any one of claims 1 to 3.
10. A speaker, A speaker, wherein the back chamber of the speaker comprises the porous composite sound absorbing material according to claim 4.
Citation Information
Patent Citations
Plastic product rubber material and preparation method thereof
CN110105745A
Sound-absorbing material preparation method, sound-absorbing material, sound production device and electronic equipment
CN111135772A
Sound-absorbing material block, preparation method thereof and loudspeaker box using sound-absorbing material block
CN114495883A
Inhale sound subassembly and be equipped with this speaker module of inhaling sound subassembly
CN205029855U
An Underpaper of a Wall
KR1020200079660A